2002
DOI: 10.1190/1.1527101
|View full text |Cite
|
Sign up to set email alerts
|

Geopressure prediction using seismic data: Current status and the road ahead

Abstract: The subject of seismic detection of abnormally high‐pressured formations has received a great deal of attention in exploration and production geophysics because of increasing exploration and production activities in frontier areas (such as the deepwater) and a need to lower cost without compromising safety and environment, and manage risk and uncertainty associated with very expensive drilling. The purpose of this review is to capture the “best practice” in this highly specialized discipline and document it. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
98
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(103 citation statements)
references
References 34 publications
2
98
0
3
Order By: Relevance
“…The effect of confining stress and pore pressure on seismic velocities is important for such geophysical applications as overpressure prediction from seismic data (Eaton, 1975;Dutta, 2002;Huffman, 2002;Sayers et al, 2002) and, more recently, for hydrocarbon production monitoring using timelapse seismic measurements (Tura and Lumley, 1999;Landrø, 2001). The dependence of seismic velocity on pressure has been confirmed for a variety of rocks by laboratory measurements of elastic wave velocities in samples with varying pressure in pore fluids (see, e.g., Wyllie et al, 1958;Todd and Simmons, 1972;Eberhart-Phillips et al, 1989;Prasad and Manghnani, 1997).…”
Section: Introductionmentioning
confidence: 87%
“…The effect of confining stress and pore pressure on seismic velocities is important for such geophysical applications as overpressure prediction from seismic data (Eaton, 1975;Dutta, 2002;Huffman, 2002;Sayers et al, 2002) and, more recently, for hydrocarbon production monitoring using timelapse seismic measurements (Tura and Lumley, 1999;Landrø, 2001). The dependence of seismic velocity on pressure has been confirmed for a variety of rocks by laboratory measurements of elastic wave velocities in samples with varying pressure in pore fluids (see, e.g., Wyllie et al, 1958;Todd and Simmons, 1972;Eberhart-Phillips et al, 1989;Prasad and Manghnani, 1997).…”
Section: Introductionmentioning
confidence: 87%
“…The velocity of a sedimentary rock in the subsurface is a function of many factors, including its depositional and burial history, lithology, texture, porosity, consolidation state, density, temperature, pore fluid type, and overpressure [Bowers, 1995;Dutta, 2002;Dvorkin and Nur, 2002;Huffman, 2002]. In considering the cause of the abrupt lateral change in seismic velocity exhibited by the bright spots, abrupt changes in most of these factors can be discounted.…”
Section: Velocity-predicted Overpressurementioning
confidence: 99%
“…We therefore assume that at a constant depth, observed velocity variations are most likely due to changes in effective stress, which are related to changes in overpressure and the bulk moduli of the materials [Carcione et al, 2003]. Dutta [2002] and Bowers [2002] showed that, at a given depth, deviations in observed seismic velocity from that predicted from a normal compaction trend could be used as an indicator of overpressure.…”
Section: Velocity-predicted Overpressurementioning
confidence: 99%
“…According to Dutta (2002), secondary low velocity semblance plots represent optimum stacking velocities for multiples, but added that it has to be established not to be as a result of lithological changes or from abnormal pore pressure. Weiglein et al (2011) also proposed that interbed multiples can be generated by stronger subsurface reflectors regarded as multiple generators at any depth, more especially, the presence of geologic contacts of differing compactions on the footwall of main boundary faults.…”
Section: Introductionmentioning
confidence: 99%